2014
DOI: 10.1155/2014/562467
|View full text |Cite
|
Sign up to set email alerts
|

IKKβ‐Targeted Anti‐Inflammatory Activities of a Butanol Fraction of Artificially Cultivated Cordyceps pruinosa Fruit Bodies

Abstract: The inhibitory activities of the Cordyceps pruinosa butanol fraction (Cp-BF) were investigated by determining inflammatory responses of lipopolysaccharide (LPS)-treated RAW264.7 macrophage cells and by evaluating HCl/ethanol (EtOH)-triggered gastric ulcers in mice. The molecular mechanisms of the inhibitory effects of Cp-BF were investigated by identifying target enzymes using biochemical and molecular biological approaches. Cp-BF strongly inhibited the production of NO and TNF-α, release of reactive oxygen sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Several studies have shown that translocation of NFκB from the cytoplasm to the nucleus may be crucial for overexpression of inflammatory mediators such as COX-2, iNOS, TNF-α, IL-1β, IL-6, IL-10 and MCP-1 [ 57 ]. The phosphorylation of IκBα and IKKβ is a vital event for NFκB activation [ 58 ]. It is established that activation of ERK may be partially responsible for LPS-induced iNOS and COX-2 expressions in RAW 264.7 macrophages [ 49 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that translocation of NFκB from the cytoplasm to the nucleus may be crucial for overexpression of inflammatory mediators such as COX-2, iNOS, TNF-α, IL-1β, IL-6, IL-10 and MCP-1 [ 57 ]. The phosphorylation of IκBα and IKKβ is a vital event for NFκB activation [ 58 ]. It is established that activation of ERK may be partially responsible for LPS-induced iNOS and COX-2 expressions in RAW 264.7 macrophages [ 49 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…All other chemicals were obtained from Sigma Chemical Co. Total or phospho-specific antibodies were purchased from Cell Signaling Technology (Beverly, MA, USA). Plasmid constructs containing AKT, IKKβ, and TBK1 were used as reported previously [24], [25], [26].…”
Section: Methodsmentioning
confidence: 99%
“…To further confirm the effects of MPP on transcriptional activation, a luciferase reporter gene activity assay was employed. HEK293 cells were co-transfected with NF-κB-Luc reporter genes under the overexpression of the adaptor molecules TRIF and MyD88, as reported previously [ 25 26 ]. Under these conditions, cells exhibited increased levels of luciferase activity up to 140- and 900-fold in the presence of TRIF and MyD88, respectively ( Figs.…”
Section: Resultsmentioning
confidence: 99%